VERSES OF NON-ACCEPTANCE OF FORGIVENESS-A STUDY IN RHETORICAL CONTEXT - "Dr. Sabahi Kazem Sakban Al-Obaidi (Scholar Express Journals, 2025)
The research seeks to study the rhetorical context and its impact on constructing meaning by analyzing the rhetorical fabric of verses about not accepting forgiveness in the Holy Qur’an. Revealing the role of context rhetorically is one of the means of clarifying and expressing meaning, due to the diversity of its connotations, its suggestive images, and its ability to diagnose abstract meanings. It seeks to know the significance of a word according to the words adjacent to it within the sentence or structure, and thus the meaning becomes apparent and its form is revealed in an effective and clear manner
Keywords: context; rhetoric; forgiveness